The impact of ethical leadership on the intention to stay among the generation-Y workforce of MNCs in Penang, Malaysia: Mediating role of employee rewards - Yoong Nian Ng; Yashar Salamzadeh (International Journal of Business Science & Applied Management (IJBSAM), 2020)
The purpose of this study is to examine the determinants of the intention to stay for Gen-Y employees of multinational corporations (MNC) in Penang, Malaysia. Specifically, this research aims to assess the impact of ethical leadership as the independent variable on employees' intention to stay as the dependent variable. In addition, the influence of employee rewards as mediator in these correlations is also examined. The survey was conducted among 138 Gen-Y employees currently employed in various MNCs in Penang, Malaysia. Data analysis is done via IBM SPSS for respondent profiling and SmartPLS for the construct variable analysis of goodness of data, reliability analysis, and the hypothesis testing of independent and mediating variables. The results show that the independent variable of ethical leadership has no positive correlation to the intention to stay of Gen-Y employees of MNCs in Penang, Malaysia. At the same time, the independent variable of employee rewards observes its dimension of pay and recognition (work appreciation) positively correlated to the dependent variable, while the dimension of promotion is surprisingly not. Accordingly, pay and recognition were found to mediate the relationship of ethical leadership to intention to stay. The subject of employee retention and turnover has been a common area of research in the field of social science, yet most of the studies have been done outside the Malaysian context. Further, most of the older studies have become irrelevant due to the dramatic demographical changes in the workforce, where the transition of the generation cohort has become more apparent in recent years. This study brings value in that the findings will close the gaps related to the dimensions proposed and is expected to help formulate a robust human capital retention strategy, critical to business sustainability.
Keywords: 650; generation-Y; ethical leadership; employee rewards; intention to stay; human capital; workforce